Mining and indigenous rights in Sweden: what is at stake and the role for legislation - Tarras-Wahlberg, Håkan; Southalan, John (Mineral Economics, 2021)
Abstract Mining and the permitting process for mineral projects in Sweden has been criticised as inadequately safeguarding the rights of Indigenous reindeer herding Sámi, who hold usufruct rights to more than half the country’s territory. There have been calls for Sweden to ratify the Indigenous and Tribal Peoples Convention (ILO 169) and to change its Mineral Law. This paper evaluates the extent of protection of Sámi rights — and not only those engaged in reindeer herding — in Sweden’s minerals permitting process. It also considers the implications if changes were made to align this process with the Indigenous-rights framework. The paper demonstrates that reindeer herding Sámi are, broadly, treated similar to landowners in the mineral projects permitting process. However, there is discrimination when it comes to being able to have a share in the benefits of a project: impacted reindeer herders have no such option whereas landowners do. Also, the permitting processes do not consider social and cultural impacts, nor are there obligations for the state to be sufficiently involved in consultation processes. Addressing the identified shortcomings would require only small changes to the Mineral Law and/or to its application and would be possible with only limited impacts on mining because the sector is not a significant user of land whilst it creates large economic values. However, extending those changes (to give parity between landowners and Sámi rights holders) in other important economic sectors which use more extensive land areas, would entail a considerable transfer of resources and associated power. Furthermore, changing the Mineral Law specifically would mean little in terms of safeguarding the rights of the majority of Sami who do not engage in reindeer herding. This suggests that calls for changes to mineral-related legislation to resolve indigenous land right issues are mis-directed or at least insufficient, and that other type of legislative change is required, fundamentally including resolving how extensive and strong the Sámi’s rights to land should be .